Hubungan Index Massa Tubuh dengan Tekanan Darah Pra Lansia - Tria Eni Rafika Devi; Vitarara Ningrum; Septi Kurniawati (Jurnal Ilmiah Kesehatan Rustida, 2021)
This study aims to analyze the Body Mass Index with Pre-elderly Blood Pressure in RT 02 RW 01 Sumberberas Village Banyuwangi in 2021. This study is a quantitative study with a cross-sectional approach, data analysis using the chi-square test. The population in this study was pre-elderly residents in RT 1 RW 2 Sumberberas Village, Banyuwangi. The research sample was taken by purposive sampling, namely 30 respondents. The independent variable in this study is body mass index (BMI) and the dependent variable is blood pressure. Based on the results of the study obtained data from 30 pre-elderly respondents with a BMI of less than 2 people showed all normal blood pressure, while with a normal BMI there were 13 people where 1 of them had normal blood pressure and 8 of them were in the prehypertension category and 4 of them were in the prehypertension category. Hypertension level I and II. Then the excess BMI / overweight / obesity as many as 15 people of which 9 people fall into the pre-hypertension category and 6 others fall into the category of Hypertension level I and II. significant positive relationship between BMI (Body Mass Index) and blood pressure. This is also supported by the descriptive results of the Crostab table which found that respondents with excess body weight tend to have pre-hypertension and grade I and II hypertension.